2011
DOI: 10.1089/rej.2010.1102
|View full text |Cite
|
Sign up to set email alerts
|

Proton MR Spectroscopy of Neural Stem Cells: Does the Proton-NMR Peak at 1.28 ppm Function As a Biomarker for Cell Type or State?

Abstract: Recently, a peak at 1.28 ppm in proton magnetic resonance spectroscopy ( 1 H-MRS) of neural stem cells (NSCs) was introduced as a noninterventional biomarker for neurogenesis in vivo. This would be an urgently needed requisite for translational studies in humans regarding the beneficial role of adult neurogenesis for the structural and functional integrity of the brain. However, many concerns have risen about the validity of the proposed signal as a specific marker for NSCs. The peak has also been related to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 43 publications
0
13
1
Order By: Relevance
“…Newly synthesized DNA of proliferating cells incorporates 18 F-FLT much the same way it incorporates halogenated thymidine analogs 5-bromo, or 5-chloro-2′-deoxyuridine (BrdU and CldU), thus enabling the use of PET for the detection of dividing cells, including neuronal progenitors [5], [7], [8]. Another imaging technique which has been tested for tracking of neurogenesis in the live brain is proton magnetic resonance spectroscopy ( 1 HMRS) [9][11]. For example, a previous 1 HMRS study applied singular value decomposition processing algorithms [10] and reported detection of neurogenesis in the hippocampus of the live rodent brain after repetitive electroconvulsive shock (ECS) treatments via increases in a lipid-like spectral signature resonating at 1.28 ppm [10], [12].…”
Section: Introductionmentioning
confidence: 99%
“…Newly synthesized DNA of proliferating cells incorporates 18 F-FLT much the same way it incorporates halogenated thymidine analogs 5-bromo, or 5-chloro-2′-deoxyuridine (BrdU and CldU), thus enabling the use of PET for the detection of dividing cells, including neuronal progenitors [5], [7], [8]. Another imaging technique which has been tested for tracking of neurogenesis in the live brain is proton magnetic resonance spectroscopy ( 1 HMRS) [9][11]. For example, a previous 1 HMRS study applied singular value decomposition processing algorithms [10] and reported detection of neurogenesis in the hippocampus of the live rodent brain after repetitive electroconvulsive shock (ECS) treatments via increases in a lipid-like spectral signature resonating at 1.28 ppm [10], [12].…”
Section: Introductionmentioning
confidence: 99%
“…Still, mI is an abundant metabolite in the adult brain and thought to act as an osmolyte, while being located in glial cells and to a lesser extent in neurons [17]. This metabolite profile therefore is useful to generally describe the NSC state, but is unlikely to specifically define NSCs per se [18]. …”
Section: Discussionmentioning
confidence: 99%
“…For example, stem cells implanted in the circle of Willis of Parkinson patients, were monitored via NMRS in a clinical magnetic resonance imaging (MRI) scanner (Brazzini et al, 2010). Moreover, mobile lipids have been detected via proton magnetic resonance in ESCs and ESC- and iPSC-derived neural stem cells (Loewenbruck et al, 2011). Choline-containing compounds linked to cell proliferation have also been monitored via NMRS in self-renewing and differentiating stem cells.…”
Section: Experimental Methods For the Analysis Of Stem Cell Populamentioning
confidence: 99%